2005
DOI: 10.1210/er.2005-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Safer Glucocorticoid Receptor Ligands

Abstract: Steroidal glucocorticoids are commonly used due to their powerful antiinflammatory activity. However, despite their excellent efficacy, severe side effects frequently limit the use of these drugs. The search for novel glucocorticoids with reduced side effects has been intensified by the discovery of new molecular details regarding the function of the glucocorticoid receptor. These new insights may pave the way for novel, safer therapies that retain the efficacy of currently prescribed steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
132
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 132 publications
0
132
0
2
Order By: Relevance
“…Intriguingly, an increasing body of evidence indicates that much of the anti-inflammatory activity of GCs is mediated by the transrepression mechanism, a finding that has been attributed largely to the repression of key inflammatory transcription factors, including AP-1 and NF-B (3-5). Meanwhile, many of the reported side effects of GC treatment have been attributed to a transactivation mechanism (32). Efforts to develop GC-based drugs that can dissociate anti-inflammatory and immunosuppressive effects from side effects have focused largely on establishing a method of dissociating the transrepression activity from the transactivation activity of the GR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, an increasing body of evidence indicates that much of the anti-inflammatory activity of GCs is mediated by the transrepression mechanism, a finding that has been attributed largely to the repression of key inflammatory transcription factors, including AP-1 and NF-B (3-5). Meanwhile, many of the reported side effects of GC treatment have been attributed to a transactivation mechanism (32). Efforts to develop GC-based drugs that can dissociate anti-inflammatory and immunosuppressive effects from side effects have focused largely on establishing a method of dissociating the transrepression activity from the transactivation activity of the GR.…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotide 5Ј-GTATAGCCTGCACTTTGTTCTGTCTAC-3Ј representing a 27-bp section of the GILZ promoter containing GRE1 (underlined) was annealed to its complement and end-labeled with 32 (Fig. S3).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, one of the main challenges in glucocorticoid pharmacology is to develop agents that can dissociate anti-inflammatory and immunosuppressive effects from these side effects. One approach was suggested by the notion that GR confers anti-inflammatory effects by transcriptional repression, whereas the side effects reflect transcriptional activation by GR (Rosen and Miner 2005). However, it has been shown that some glucocorticoid-activated genes, such as annexin I, are important in the anti-inflammatory effect Roviezzo et al 2002), whereas some glucocorticoid-repressed genes, such as endothelial nitric oxide synthase (eNOS) (Wallerath et al 1999(Wallerath et al , 2004Schafer et al 2005), are associated with deleterious side effects.…”
mentioning
confidence: 99%
“…Selective nuclear receptor modulators (SNuRMs) which are able to elicit a specific biological response at the expense of the other activities that the natural ligand may induce (Gronemeyer et al, 2004) have been described for the estrogen receptor (Robertson, 2004) and the glucocorticoid receptor (Rosen & Miner, 2005) among others. The nematode has undergone a dramatic expansion in the NHR superfamily with 284 predicted receptors compared with 48 in humans (Sluder et al, 1999).…”
Section: Endocrine Targets For Pharmacological Interventionmentioning
confidence: 99%